Dahili Aciller - Borazan, İsmail and Top, Ahmet Ali and Ferhatlar, Mehmet Esat and Şentürk, Mücahit and Danış, Faruk and Oymak, M.Server and Karcıoğlu, Özgür and Beşer, Zafer and Karabay, Onur and Kabakçı, Ahmet and Özensoy, Habibe Selmin and Kemancı, Aykut and Çavar, Orhan and Bildik, Büşra and Çakmak, Onur and Koca, Yavuzselim and Koca, Senem and Ergün Süzer, Neslihan and Yılmaz, Alp and Yiğiter, Büşra and Balcı, Serdal and Şirin, İlker and Ahçı Yılmaz, Seda and Aydın, Erdem and Çelebi, Melis and Doğan, İrem and Oğuz, Seda and Kocabaş, Yeliz and Akdoğan, Halil İbrahim and; rlık, Mahmut Arda and; çi, Mert and, Emre and, Begüm and; gan, Fethi Ahmet and; rk, Berkant (Academician Publishing Book DOI Portal, 2024)
-